Circulating oxysterol metabolites as potential new surrogate markers in patients with hormone receptor-positive breast cancer: Results of the OXYTAM study. Issue 169 (May 2017) - Dalenc, Florence; Iuliano, Luiggi; Filleron, Thomas; Zerbinati, Chiara; Voisin, Maud; Arellano, Cécile; Chatelut, Etienne; Marquet, Pierre; Samadi, Mohammad; Roché, Henri; Poirot, Marc; Silvente-Poirot, Sandrine
Graphical abstract: Highlights: Patients with breast cancers were treated with tamoxifen or aromatase inhibitors. Tamoxifen and aromatase inhibitors increased the level of 5, 6-epoxycholesterol. Aromatase inhibitors increased the levels of 25- and 27-hydroxycholesterol. Abstract: Accumulating evidence indicates that cholesterol oxygenation products, also known as oxysterols (OS), are involved in breast cancer (BC) promotion. The impact of Tam, as well as aromatase inhibitors (AI), an alternative BC endocrine therapy (ET), on OS metabolism in patients is currently unknown. We conducted a prospective clinical study in BC patients receiving Tam (n = 15) or AI (n = 14) in adjuvant or in metastatic settings. The primary end point was the feasibility of detecting and quantifying 11 different OS in the circulation of patients before and after 28 days of treatment with Tam or AI. Key secondary end points were the measurements of variations in the concentrations of OS according to differences between patients and treatments. OS profiling in the serum of patients was determined by gas chromatography coupled to mass spectrometry. OS profiling was conducted in all patients both at baseline and during treatment regimens. An important inter-individual variability was observed for each OS. Interestingly 5, 6β-epoxycholesterol relative concentrations significantly increased in the entire population (p = 0.0109), while no increase in Cholestane-triol (CT) levels was measured. Interestingly, we found that, in contrast to AI, Tam therapy significantly decreased blood levels of 24-hydroxycholesterol (24-HC), 7α-HC and 25-HC (a tumor promoter) (p = 0.0007, p = 0.0231 and p = 0.0231, respectively), whereas 4β-HC levels increased (p = 0.0010). Interestingly, levels of 27-HC (a tumor promoter) significantly increased in response to AI (p = 0.0342), but not Tam treatment. According to these results, specific OS are promising candidate markers of Tam and AI efficacy. Thus, further clinical investigations are needed to confirm the use of oxysterols as biomarkers of both prognosis and/or the efficacy of ET.